Television advertisement effectiveness in food industry among centennials / Intan Syafinaz Mat Shafie... [et al.] - Mat Shafie, Intan Syafinaz; Mohammad Yunus, Yuslina Liza; Jamil, Nur Izzah; Musa, Aini Hayati (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Television (TV) advertisements have become one of the most powerful marketing tools in attracting their audience to become potential customers. They are widely used among food industry locally and also internationally. This study is conducted to identify the factors that contribute to an effective TV advertisement in food industry among centennials using predictive analysis. The aims of this study are to; 1) Identify significant factors; Attractive Visual, Persuasive Message and Repetition of Advertisement to the Effectiveness of TV advertisements in food industry. 2) Identify the most contribute significant factors; Attractive Visual, Persuasive Message and Repetition of Advertisement to the Effectiveness of TV advertisements in food industry. Thus, it was tested to 300 respondents in Shah Alam area using convenient sampling technique. Preliminary analysis included reliability analysis, checking for the correlation, multiple linear regression requirement and R-Square score. Correlation analysis shows that there was a significant positive linear relationship between attractive visuals, persuasive message and repetition of advertisements towards Effectiveness of TV advertisements in food industry. Among independent variables entered into the model, persuasive message (t=7.474, p-value=0.000<0.05) and repetition of advertisements (t=6.038, p-value=0.000<0.05) made statistically significant contributions towards effectiveness of TV advertisements in food industry. In terms of importance, independent variable of persuasive message (Beta=0.416) made the largest contribution to the model. Consumers believed these two variables do benefit in delivering the message more accurately. Based on these analyses, it was found that all variables have relationships with the effectiveness of TV advertisement and met the research objectives of this study.